AN ANALYSIS OF THE MECHANISM OF REMOVAL OF JUDGES OF THE HIGHER JUDICIARY IN INDIA - Altaf, Mir Mubashir; Dar, Mohd. Ayub (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The higher judiciary in India is one of the most powerful judiciaries of the world owing to the abiding public faith in the integrity and impartiality of its judges. Over the years the higher judiciary in India through its creative constitutional adjudication has set out a robust rights-based regime for the citizenry. A gamut of judicial dictums has carved out a bundle of rights from Part 3rd of the Constitution by adopting a purposive approach to constitutional interpretation. This activist role played by the judiciary largely depends on the broad powers vested in the judiciary within the Constitution, especially about its power to do complete justice within the rubric of Article 142 of the Constitution. However, with ascendancy in judicial power, there has been a clamor for making the judges of the higher judiciary accountable, especially in light of a series of allegations of corruption against judges over the past decade or so. This paper attempts to analyze the mechanisms of judicial accountability in India, especially concerning the process of removing the judges set out in the Constitution.